Story Development - Brandon Telg; Jaron Jones; Ricky Telg (EDIS)
Stories let you share who you are with the world. Storytelling can help develop an organization’s identity, improve interactions with the public, and foster teamwork. This 2-page fact sheet covers the basics of good storytelling and strategies for crafting an engaging story. Written by Brandon Telg, Jaron Jones, and Ricky Telg, and published by the UF Department of Agricultural Education and Communication, July 2015. (Photo credit: elwynn1130/iStock/Thinkstock.com)